MALAKOK SEBAGAI SYARAT UNTUK MENJADI WARGA MASYARAKAT DI NAGARI TANJUNG SANI KABUPATEN AGAM - Hafizah Hafizah (STKIP Pesisir Selatan, 2017)
This study attempts to express a meaning malakok for the citizens who come from outside the nagari tanjung sani , requirements and the process malakok , conflicts that have occurred if not malakok in nagari tanjung sani , kabupaten agam .The kind of research is the type study kasus.tekhnik election informants uses the method ( purposive sampling ) .hasil research shows that malakok is a prerequisite to gain citizens for recognized where i new .It means for residents who come from outside the nagari tanjung sani and to their children is that they are valued as well as having tribe and niniak mamak when married can get and can complained to niniak mamak and the community when things go wrong .As for requirements and procedures malakok in the nagari tanjung sani among others. ( 1 ) there give gold of 2 to 5 gold in carano filled with siriah. ( 2 ) there are also by cutting of animals as notification to the people a lot that children the a have malakok and official as a son and nephews the in the.When the requirements been fulfilled so come 4 priest to the handover of the in the child.Problems often emerge if newcomers not doing malakok so they commit married with local residents because they are considered a person who is not polysyllabic and not berniniak mamak and do not have the origin of, then newcomers embarrassed and shutting out because they could no implement customary malakok in nagari tanjung sani.